Temperature dependence of hot luminescence in solid xenon: theory and experiment: Spectroscopy in Cryocrystals and Matrices - Selg, Matti; Kink, Rein (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Vibrational relaxation of self-trapped excitons in solid xenon has been investigated both experimentally and theoretically. Hot luminescence spectra of the crystal have been measured in awide temperature range (from liquid helium temperature to 100 K), using x-ray and two-photon excimer laser (ArF and KrF) excitation. The theoretical analysis is based on a recent nonperturbative relaxation theory and on a rigorous quantum mechanical Franck—Condon approach.